Análise espacial da precipitação pluvial e eventos extremos secos na bacia hidrográfica do rio São Francisco - Brasil, série histórica de 1985 a 2018 - Petrucci, Eduardo (2022)
The São Francisco River Basin (SFRB) is one of the most important Brazilian basins, where more than 20 million people live in 508 municipalities, spread over eight federation units, of whom São Francisco River, with approximately 2,700 km, as its main drainage. For planning purposes, the SFRB is subdivided into four physiographic regions, each one with socioeconomic and natural peculiarities. The objective of this thesis is to analyze the spatial behavior of rainfall and extreme drought events in the SFRB. To do so, rainfall data from 244 rainfall stations (211 in the interior and 33 around the basin) were used monthly from HIDROWEB and the National Water Agency (ANA), concerning historical series from 1985 to 2018. In order to evaluate the spatial dependence of precipitation (semivariogram) as well as the estimation of values (Ordinary Kriging and respective cross-validation) for the places devoid of these, geostatistical techniques were applied with respective removal of trend by spatial location. Through basic statistics, monthly averages of precipitation were used, and annuals totals and annual averages as well. For the analysis of droughts, the Extreme Precipitation Deficits (DEp) were calculated [using the Standardized Index of Rainfall Droughts (IESP)], the Dry Months (monthly rainfall < 1.0 mm); and the Negative Deviations (NDs). For the spatial analysis of the annual average precipitation, the QGIS software was used; for data modeling (geostatistics) AR2GEMS/SGeMS and GS+ software was used. The semivariogram models produced were exponential (annual average precipitation) and spherical (dry months and negative deviations) and, for the kriging evaluation, cross-validation was used. As a result, it was verified that the annual precipitation varies between 1,703.5 mm and 273,0 mm, being higher in the ASF region and lower in the SMSF. Regarding the DEp, 258 occurrences were determined, mainly from 2015 onwards, with the years 2017 and 2018 concentrating 83.3% of rainfall droughts. The higher number of monthly occurrences and the longest sequence of consecutive months of droughts occurred in the ASF mesoregion. In respect to the Dry Months, there was no defined patter of annual quantities, with the most recurrent years being: 2007, 2017 and 2011, with 1,779, 1,679 and 1,564 dry months, respectively. The largest amount (106 months) and the longest consecutive sequence (9 months) was recorded in the SMSF. In relation to DNs, the highest number of occurrences was 96 months in multiple stations (40), in the ASF, SMSF and BSF regions. The longest sequence of consecutive months occurred in SMSF, totaling 16 months, with 2014 being the most recurrent. Overall, during the 2010s, there was a great variation of annual precipitation, alternating between rainy years and extremely dry years, which was revealed when drought verification methods were applied, which concentrated most of the occurrences of pluviometrical droughts, compared to previous decades.